Nurses as educators in the comprehensive heart failure care programme-Are we ready for it? - Dorota Krówczyńska; Beata Jankowska‐Polańska (Wiley, 2020)
Abstract Aim To assess education frequency and nurses' comfort when educating patients hospitalized in different hospital units to prepare them for self‐care. Design A cross‐sectional survey. The study included nurses working in units where HF patients were hospitalized. Results The average score for comfort of education was 5.43 (between "slightly comfortable" and "very comfortable"). The most comfortable topics were "Daily weight monitoring" (5.81 ± 1.25), "Signs/symptoms of worsening condition" (5.77 ± 1.19) and "Fluid restriction" (5.76 ± 1.23). The respondents felt least comfortable when teaching about "Medications" (5.06 ± 1.35) and "Low‐sodium diet" (5.31 ± 1.42). The mean score obtained for education frequency was 5.21 (SD 2.51). The nurses most frequently educated their patients on such topics as "Daily weight monitoring" (5.82), "Signs/symptoms of worsening condition" (5.9) and "Fluid restriction" (5.92). Conclusions Polish nurses are not ready to perform comprehensive HF care tasks without preparation.